ERROR ANALYSIS ON GRAMMATICAL ASPECTS OF STUDENTS NARRATIVE WRITING (A CASE STUDY AT ECONOMICS AND BUSINESS OF MALIKUSSALEH UNIVERSITY IN ACADEMIC YEAR 2014/2015) - Irawati, Henny (Getsempena English Education Journal, 2015)
The objective of this research is to find out the most typical words which are made by the students in writing. Based on the objective of the research, the writer uses a narrative method. In collecting the data, the writer administers a kind of writing test to students. The research is conducted to first semester of Economics and business faculty of Malikussaleh University. The writer took the correspondent on in 40 students by random sampling. The material is tested based on the English syllabus. Then, the writer analyzes the writing errors done by students. The results of research show that errors on word choice are the most typical errors made by students with 37 or 19.2% and then word order with 32 or 16.6%, followed by verb tenses with 29 or 15.0%. From the results of the research, the writer can conclude that the most typical errors on studentâs narrative writing skill at first semester of Economics and Business is errors on word choice. It indicated that the most students need more treatment and remedial teaching from the lecturer towards their errors on English writing right away and it implies that the students still need more practice in order to develop their writing skill.Â Key Words: Error Analysis, Narrative Writing